Synthesis (Montage) in Contemporary Arabic Poetry (Journal of the College of Basic Education, 2023)
Language is a social product whose purpose is understanding and benefit, which are the reason for its existence.The alarming shout of neanderthals was first an instinctive reaction.)Physiological) Before becoming a symbol, it retains its meaning independent of the circumstances for its speaker. LanguageA system of symbols or a laboratory system of rules in the minds of speakers of a language, and if they are not components ofIf this system is clear in their minds, understanding and linguistic communication between them is severed, but the languagePoetics has its own system within the general linguistic system that the poet knows and the recipients know.The poet knows it through the knowledge of creation and use, while the recipient knows it through receiving and receiving, and from hereThe common saying is that poetry is a “language within a language” or a “language beyond language”.